Epidemiology of Injuries in Sports - Canata, Gian Luigi; Jones, Henrique; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2022)
This concise yet comprehensive book covers epidemiology of injuries in 24 different sports ranging from football, volleyball, athletics, to less explored ones, like archery and Formula 1. For each discipline the authors present and analyze the sport$1 (Bs main characteristics, physiological and biomechanical demands on athletes, epidemiology of injuries, prevention strategies, rehabilitation and return to play. Based on an updated overview of sport specific data, this book equips the reader with a solid understanding of sports injury epidemiology and its importance for the implementation of preventive measures. Written in collaboration with ESSKA by almost 100 international experts, sharing the belief that prevention is the first mission of sports medicine, this book is an excellent source of knowledge for sports physicians, researchers, residents, fellows and trainers alike.s
1 Archery -- 2 Athletics: jumping disciplines -- 3 Long-distance running -- 4 Athletics: sprint disciplines -- 5 Throwing athletes -- 6 Basketball -- 7 Cycling -- 8 Extreme Sports -- 9. Field Hockey -- 10 Football -- 11 Youth Football -- 12 Handball -- 13 Ice Hockey -- 14 Olympics -- 15 F 1 -- 16 Motocross.-17 Rugby -- 18 Ski -- 19 Alpine Ski.-20 Cross Country Skiing -- 21 Tennis.-22 Volleyball -- 23 Waterpolo -- 24 Wrestling.
Keywords: Sports medicine; Orthopedics; Physical therapy; Sports Medicine; Orthopaedics; Physiotherapy; Athletic Injuries -- epidemiology; Sports Medicine